A PROPOSED CASE STUDY FIELD RESEARCH METHODOLOGY TO TEST COST DRIVERS: AN EXAMPLE OF PROPOSED FIELD STUDY AT A NUCLEAR MEDICINE UNIT - Liu, Min (International Journal of Accounting & Finance Review, 2021)
This paper illustrates how to use case study method to conduct the cost driver research at hospitals by identifying activity-based cost drivers at the nuclear medicine unit (NMU) of a teaching hospital. I argue that recognizing the activity-based cost could improve the accuracy of estimating costs by identifying the underutilized resources and value-added and non-value-added cost drivers, to reduce non-value-added costs; thereby, facilitating the management to make better informed managerial decisions (e.g., improving pricing practices and using resources more efficiently). Therefore, I believe that this study may provide a useful inference to hospitals to improve the quality and quantity of the service, which they (or would) provide. Furthermore, this paper possibly provides an informative research methodology for researchers by showing how to extend the current literature by applying the same cost analysis research model on a different dataset for the health care industry research. JEL Classification Codes: M10, M11, M40, M41.